Experimental study of organic Rankine cycle in the presence of non-condensable gases - Li, Jing; Gao, Guangtao; Li, Pengcheng; Pei, Gang; Huang, Hulin; Su, Yuehong; Ji, Jie (Elsevier, 2018)
Non-condensable gases (NCGs) are inevitable in organic Rankine cycle (ORC) system, and they have adverse impacts. A small-scale ORC test platform using scroll expander and R123 was constructed to investigate the NCGs effect. The expander backpressure (i.e. condenser outlet pressure) and electricity output were examined on different conditions of NCGs mass fraction (xNCG), hot side temperature (Th) and condensation temperature (Tc). Two new parameters, namely reduced coefficient of pressure ratio (RCOPR) and filling ratio of reservoir (FROR), were proposed to reveal the mechanism of ORC performance degradation in the presence of NCGs. The results show that the partial pressure of NCGs (PNCG) in reservoir at work differed from that at static state. Unlike R123, NCGs were blocked by the reservoir and had no access to the pump. The accumulation of NCGs led to unexpected expander backpressure, which could be 0.68 bar higher than the saturation pressure when Th = 140 °C, Tc = 50 °C and xNCG = 1.3%. PNCG generally increased as FROR rose. The FROR changed with Th, Tc and R123 mass flow rate. The relative increment in electricity output of the ORC with xNCG = 1.3% over that with xNCG = 12% was significant, and could reach 114% when Th = 100 °C and Tc = 50 °C.